1997
DOI: 10.1001/jama.1997.03540350054033
|View full text |Cite
|
Sign up to set email alerts
|

A Coccidioidomycosis Outbreak Following the Northridge, Calif, Earthquake

Abstract: Both the location and timing of cases strongly suggest that the coccidioidomycosis outbreak in Ventura County was caused when arthrospores were spread in dust clouds generated by the earthquake. This is the first report of a coccidioidomycosis outbreak following an earthquake. Public and physician awareness, especially in endemic areas following similar dust cloud-generating events, may result in prevention and early recognition of acute coccidioidomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(93 citation statements)
references
References 16 publications
0
91
0
2
Order By: Relevance
“…Sievers (266), in his study of disseminated coccidioidomycosis in the American Indian population, found that children younger than 5 years and adults older than 50 years were significantly more susceptible than persons aged 6 through 49 years. An increased susceptibility of older persons was observed in the outbreak in Ventura County following the Northridge earthquake (260), in the 3-year coccidioidomycosis epidemic that started in San Joaquin Valley in 1991 (12,157) as well as a subsequent follow-up covering the period from January 1995 through December 1996 (248), and in analyses of cases of coccidioidomycosis in Arizona (182). In the last study, elderly persons who had recently relocated to Arizona appeared to be at the highest risk.…”
Section: Risk Factors For Severe Disseminated Coccidioidomycosismentioning
confidence: 93%
See 3 more Smart Citations
“…Sievers (266), in his study of disseminated coccidioidomycosis in the American Indian population, found that children younger than 5 years and adults older than 50 years were significantly more susceptible than persons aged 6 through 49 years. An increased susceptibility of older persons was observed in the outbreak in Ventura County following the Northridge earthquake (260), in the 3-year coccidioidomycosis epidemic that started in San Joaquin Valley in 1991 (12,157) as well as a subsequent follow-up covering the period from January 1995 through December 1996 (248), and in analyses of cases of coccidioidomycosis in Arizona (182). In the last study, elderly persons who had recently relocated to Arizona appeared to be at the highest risk.…”
Section: Risk Factors For Severe Disseminated Coccidioidomycosismentioning
confidence: 93%
“…Coccidioidomycosis is considered to be a reemerging disease because of the dramatic increase in the number of cases during the early part of the past decade (47,52,105,157,207,219,260,282). Between 1991 and 1994, there was a notable increase of new cases in California, in particular in Kern and Tulare counties in the southern part of the San Joaquin Valley (219).…”
Section: Clinical Manifestations Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental conditions, including drought, precipitation, temperature, and wind speed, appear to have an impact on coccidioidomycois incidence [Comrie 2005]. Previous studies have hypothesized that Coccidioides spores (vegetative fungal cells in a resting state) are most abundant in the soil after heavy rains and may be most effectively dispersed during dry, hot periods, such as prolonged droughts [Smith et al 1946;Schneider et al 1997;Kolivras and Comrie 2003;Comrie 2005]. Thus, increased incidence of infection often occurs after a heavy wet season followed by a prolonged dry spell [Zender and Talamantes 2005].…”
Section: Appendix A: Coccidioides Coccidioidesmentioning
confidence: 99%